The Preparation, Properties, and Characterization of Octenyl Succinic Anhydride-Modified Turmeric Starches and Their Emulsification for Pickering Emulsions - Lijuan Fu; Hongfei Chi; Hang Wei; Biao Huang; Yueyue Qiang; Mengzhu Shi; Ling Fang; Jianwei Fu (Foods)
Turmeric has extensive applications in various fields, including food and medicine. However, research on turmeric starch remains relatively scarce. There is a significant lack of in-depth studies on its processing properties and starch modification abilities. In this context, octenyl succinic anhydride (OSA)-modified turmeric starches (O-MTSs) were synthesized. Subsequently, a comprehensive investigation was carried out, including property analysis, characterization, and evaluation of the emulsifying capacity. The alterations in solubility, swelling degree, syneresis, and transparency of turmeric starches before and after modification were systematically studied. The characterization of O-MTSs was conducted using a scanning electron microscope (SEM), particle size analysis, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetric analysis. The possibility of using O-MTS as an emulsifier to prepare Pickering emulsions was explored. The results show that O-MTS had better solubility, swelling degree, syneresis, and transparency compared to turmeric starches (TSs). The O-MTS retained a relatively intact morphology, but its particle size slightly increased, and the characteristic peak at 995 cm−1 shifted to some extent. The relative crystallinity decreased from 32.59% to 18.39%, and the water-binding capacity of O-MTSs improved accordingly. O-MTSs could better stabilize Pickering emulsions as an emulsifier compared to TSs. With the increase in the degree of substitution (DS) and concentration of the O-MTS, its emulsification index (EI) demonstrated an upward trend.